Monoclonal antibodies against the Drosophila nervous system. - Fujita, S C (1982)
A panel of 148 monoclonal antibodies directed against Drosophila neural antigens has been prepared by using mice immunized with homogenates of Drosophila tissue. Antibodies were screened immunohistochemically on cryostat sections of fly heads. A large diversity of staining patterns was observed. Some antigens were broadly distributed among tissues; others were highly specific to nerve fibers, neuropil, muscle, the tracheal system, cell nuclei, photoreceptors, or other structures. The antigens for many of the antibodies have been identified on immunoblots. Monoclonal antibodies that identify specific molecules within the nervous system should prove useful in the study of the molecular genetics of neural development.